Efektivitas Tata Kelola Penanganan Anak Stunting oleh Dokter dan Tenaga Kesehatan di Kota Yogyakarta - Dhinta Ekka Wardhani; Velysia Ratnawati Suparwito; Salim, Agus (CV Insan Kreasi Media, 2024)
The governance management of stunting children in Yogyakarta is carried out through the Stunting Case Audit (AKS) program. This program was implemented as an effort to meet the zero stunting target of Yogyakarta City through early intervention to reduce and prevent the appearance of similar cases from the audited areas. To find out that the AKS program has succeeded in achieving its goals, it is necessary to conduct a study to examine the effectiveness of the AKS program. This research is using a qualitative approach by comparing the suitability of program implementation with indicators of effectiveness. The results of this research explain that from the four effectiveness indicators used, only one indicator met the implementation of AKS. Indicators of timeliness have been met, while indicators of target accuracy, goal attainment and the emergence of expected results have not been met the expectation.